2009
DOI: 10.1080/03630240903424012
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Group Weight Loss Efforts Among Lesbians

Abstract: Participants had long histories of shame and fear surrounding weight loss attempts. Weight loss group participants needed cultural connectivity and a sense of safety and acceptance to address issues contributing to weight gain and in order to lose weight and maintain weight loss. Although more research is needed before implementation of a sexual minority women-specific weight loss program, these data are the basis for further exploration into the development of such a program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 12 publications
0
35
0
Order By: Relevance
“…Commonly, many people (not distinguishing between heterosexual and sexual minority) who have resolved to lose weight feel a sense of fear and dread when anticipating confronting the difficult issues that surround weight loss (Abraham, Von Lojewski, Anderson, Clarke, & Russell, 2009;Landau, 2001). For many lesbians, this sense of dread is compounded with a sense of fear surrounding disclosure of sexual identity when entering a group of unfamiliar people (Fogel et al, 2009). In the qualitative component of this descriptive study a model was identified that depicted what the vast majority of participants experienced in previous weigh loss attempts (Fogel et al, 2009).…”
Section: Review Of the Literaturementioning
confidence: 96%
See 4 more Smart Citations
“…Commonly, many people (not distinguishing between heterosexual and sexual minority) who have resolved to lose weight feel a sense of fear and dread when anticipating confronting the difficult issues that surround weight loss (Abraham, Von Lojewski, Anderson, Clarke, & Russell, 2009;Landau, 2001). For many lesbians, this sense of dread is compounded with a sense of fear surrounding disclosure of sexual identity when entering a group of unfamiliar people (Fogel et al, 2009). In the qualitative component of this descriptive study a model was identified that depicted what the vast majority of participants experienced in previous weigh loss attempts (Fogel et al, 2009).…”
Section: Review Of the Literaturementioning
confidence: 96%
“…For many lesbians, this sense of dread is compounded with a sense of fear surrounding disclosure of sexual identity when entering a group of unfamiliar people (Fogel et al, 2009). In the qualitative component of this descriptive study a model was identified that depicted what the vast majority of participants experienced in previous weigh loss attempts (Fogel et al, 2009). These experiences led the participants to seek out a predominantly lesbian weight loss group (PLWLG).…”
Section: Review Of the Literaturementioning
confidence: 98%
See 3 more Smart Citations